Cryo-EM reveals that Escherichia coli tRNA-transglycosylase can bind and act upon two tRNAs - Alexander Harjung; Ember M. Ruth; Mariusz Matyszewski; Jaehee Park; Caroline Knittel; Evan McCormack; Neal K. Devaraj (Proceedings of the National Academy of Sciences, 2026)
Bacterial tRNA-guanine transglycosylases (TGT) are essential enzymes involved in tRNA modification, contributing to the virulence of multiple pathogens. TGT from Escherichia coli was the first protein of this family to be isolated and purified, and as such has served as a model enzyme for the biochemical characterization of TGTs. E. coli TGT is also one of the most disease-relevant TGTs, sharing high sequence identity with TGTs from several human pathogenic bacteria, including Shigella spp. and Salmonella spp. Notably, TGTs from some Shigella strains are sequence-identical to the E. coli enzyme. In addition, as a highly promiscuous enzyme, E. coli TGT has found use as an RNA-modification tool in chemical biology, enabling site-specific covalent RNA modification in vitro and in vivo. For these reasons, there has been significant interest in solving the structure of E. coli TGT. However, crystallization of E. coli TGT has proven difficult, and to date, structural insights have relied on surrogate TGT enzymes from other organisms. Here, we present the cryo-EM structure of E. coli TGT and its covalent intermediate with a full-length tRNA. Unexpectedly, the structure reveals that the E. coli TGT dimer binds and acts upon two tRNAs, which is unlike all other known TGTs. Closer analysis of the TGT–tRNA complex reveals several important interactions outside of the enzyme’s active site, that facilitate RNA binding and stabilize the conformational change of the tRNA anticodon loop. Based on these structural insights, we were able to design improved, high-affinity, TGT substrate RNA hairpins.